1994
DOI: 10.1002/art.1780370915
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte function—associated antigen 1 overexpression and t cell autoreactivity

Abstract: Objective. To determine if DNA methylation inhibitors make T cells autoreactive by inducing lymphocyte function-associated antigen type 1 (LFA-1) ( C D l l d CD18) overexpression.Methods. T cell clones were treated with 3 distinct DNA methylation inhibitors or were stably transfected with a CD18 cDNA in a mammalian expression vector, and the effects on LFA-1 expression and activation requirements were examined.Results. LFA-1 overexpression, caused by DNA methylation inhibitors or by transfection, correlates wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
72
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 112 publications
(77 citation statements)
references
References 26 publications
4
72
0
1
Order By: Relevance
“…This gene was selected because it is overexpressed following treatment with DNA methylation inhibitors (6-9), because LFA-1 overexpression causes T cell autoreactivity in vitro and a lupus-like disease in vivo (4,8), and because a similar LFA-1 overexpression occurs on an autoreactive T cell subset in lupus (9,10). It is likely that DNA hypomethylation affects other T cell genes in addition to ITGAL, and recent studies using oligonucleotide arrays have demonstrated that transcription of Ͼ100 known genes increases following treatment with 5-azaC, including genes of possible relevance to lupus, such as perforin and CD70 (Richardson B: unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This gene was selected because it is overexpressed following treatment with DNA methylation inhibitors (6-9), because LFA-1 overexpression causes T cell autoreactivity in vitro and a lupus-like disease in vivo (4,8), and because a similar LFA-1 overexpression occurs on an autoreactive T cell subset in lupus (9,10). It is likely that DNA hypomethylation affects other T cell genes in addition to ITGAL, and recent studies using oligonucleotide arrays have demonstrated that transcription of Ͼ100 known genes increases following treatment with 5-azaC, including genes of possible relevance to lupus, such as perforin and CD70 (Richardson B: unpublished observations).…”
Section: Discussionmentioning
confidence: 99%
“…Plasmid DNA was introduced into Jurkat cells by electroporation using a modification of previously described protocols (4,8). Twenty-four hours later, the cells were washed twice, suspended in 400 l reporter lysis buffer (Promega), and lysed by freeze-thaw.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…10 CD4+ T cells treated with DNA methylation inhibitors overexpress LFA-1 (CD11a/CD18) and become autoreactive, responding to self-class II MHC without the addition of exogenous antigen. 11 The autoreactivity is due to demethylation and overexpression of the ITGAL (CD11a) gene, 12,13 and T cells overexpressing LFA-1 by transfection display identical autoreactivity. 14 Hypomethylated, autoreactive CD4+ cells also spontaneously kill autologous macrophages (Mø), causing release of antigenic nucleosomes through mechanisms including demethylation and subsequent overexpression of the PRF1 (perforin) gene.…”
Section: Introductionmentioning
confidence: 99%